Nano Online 2016
DOI: 10.1515/nano.11671_2015.327
|View full text |Cite
|
Sign up to set email alerts
|

A New Phase Change Material Based on Potassium Nitrate with Silica and Alumina Nanoparticles for Thermal Energy Storage

Abstract: In this study different nanofluids with phase change behavior were developed by mixing a molten salt base fluid (KNO 3 selected as phase change material) with nanoparticles using the direct synthesis method. The thermal properties of the nanofluids obtained were investigated. Following the improvement in the specific heat achieved, these nanofluids can be used in concentrating solar plants with a reduction of storage material. The nanoparticles used (1.0 wt.%) were silica (SiO 2 ), alumina (Al 2 O 3 ), and a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…have been performed to identify the mechanism underlying the specific heat increase in the molten salt nanofluids [18][19][20][21][22]. Chieruzzi et al enhanced the specific heat of a binary nitrate (NaNO 3 -KNO 3 ) by dispersing various nanoparticles (Al 2 O 3 , SiO 2 , TiO 2 , and SiO 2 -Al 2 O 3 ) [23,24]. The enhanced specific heat of the molten salt nanofluids was explained in various ways, e.g., electron microscope images and molecular dynamics simulation [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…have been performed to identify the mechanism underlying the specific heat increase in the molten salt nanofluids [18][19][20][21][22]. Chieruzzi et al enhanced the specific heat of a binary nitrate (NaNO 3 -KNO 3 ) by dispersing various nanoparticles (Al 2 O 3 , SiO 2 , TiO 2 , and SiO 2 -Al 2 O 3 ) [23,24]. The enhanced specific heat of the molten salt nanofluids was explained in various ways, e.g., electron microscope images and molecular dynamics simulation [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, another HSM was developed through water solution method by using KNO 3 as molten salt (melting point of 334°C) and 1 wt.% of SiO 2 , Al 2 O 3 , and a mixture of SiO 2 -Al 2 O 3 as nanoparticles [23]. The HSM has an increased specific heat with silica and silica-alumina nanoparticles (+9.5% and +4.7%, respectively).…”
Section: Heat Storage Materialsmentioning
confidence: 99%
“…However, some studies performed by University of Perugia reported an increase of 15% mainly with silica-alumina nanoparticles in nitrate mixture [22] and also in KNO 3 as molten salt having a melting point of 334°C (the latent heat increased by 12%). In both studies, the NEPCMs were produced in water solution [23]. It was shown that the stored heat of molten salts as NaNO 3 -KNO 3 [22] and KNO 3 [23] is increased with the addition of 1.0 wt.% of SiO 2 -Al 2 O 3 and SiO 2 .…”
Section: Heat Storage Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing nanoparticle into a base fluid to improve its thermophysical properties, termed as 'nanofluid', has been extensively studied in the past [4][5][6][7][8]. Recently, similar concept was used to disperse suitable particles in solar salts to improve their thermal energy storage capacity [9][10][11][12][13][14][15][16][17], hence termed as 'nano-salt' here to consider the dispersion in both solid and liquid phases suitable for TES applications.. A majority of the work [18][19][20][21][22][23][24] showed that the specific heat of nano-salt was increased, except the experimental results of Lu et al [20]. For example, Shin and Banerjee [4] dispersed silica nanoparticles into alkali metal chloride salt eutectics, and reported a c p enhancement of 14.5% at 1 wt % particle concentration.…”
Section: Introductionmentioning
confidence: 99%